Polymorphism rs1761667 in the CD36 Gene Is Associated to Changes in Fatty Acid Metabolism and Circulating Endocannabinoid Levels Distinctively in Normal Weight and Obese Subjects - Melis, Melania; Carta, Gianfranca; Pintus, Stefano; Pintus, Paolo; Piras, Carla A.; Murru, Elisabetta; Manca, Claudia; Di Marzo, Vincenzo; Banni, Sebastiano; Tomassini Barbarossa, Iole (Frontiers in Physiology, 2017)
The multifunctional CD36 scavenger receptor facilitates fatty acid (FA) uptake and oxidation and it has been involved in the pathophysiology related to dysfunctional FA metabolism. The common variant in the CD36 gene, rs1761667 (A/G), whose allele A is characterized by a reduced protein expression, has been associated with taste sensitivity to and preference for fat. We therefore aimed at evaluating whether the CD36 polymorphism may influence fatty acid metabolism and endocannabinoid biosynthesis in normal weight (NW) and obese (OB) subjects. Red blood cell (RBC) fatty acid composition, and plasma endocannabinoid levels were determined. In NW subjects with AA genotype was found a marked reduction of RBC saturated fatty acids and palmitic/linoleic ratio (PA/LA), considered as de novo lipogenesis (DNL) biomarkers. Remarkably, to the reduction of DNL biomarkers corresponded an increase of omega-6 index, an indirect marker of the impact on fatty acid metabolism of dietary omega-6 fatty acids, endocannabinoid levels and a higher waist/hip ratio. The presence of the G allele was instead associated with increased endocannabinoid plasma levels and a trend for increased waist/hip ratio in obese subjects, even though exhibited decreased BMI with respect to those with AA genotype. These data indicate that the CD36 polymorphism, rs1761667, leads to a distinct metabolic pattern in NW and in OB subjects. Therefore, their determination may be crucial in developing personalized therapeutic strategies for ameliorating dyslipidemia and other metabolic disorders.